SISTEM KEYAKINAN DAN AJARAN ISLAM ABOGE - Falinda Falinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This article discusses and analyzes the belief systems of AbogeIslamic community. In Java, Islam has a unique variant. It is correlatedwith how Islam spreads and process its acculturation with existed Javaneseculture. To examine the belief systems and practices of this ritual, thedata collected through observation, interviews, and documentation. Thisarticle suggests that religious teachings and beliefs of the Aboge JavaneseMuslim Community are taught for generations. Aboge adherents say thatthe core of their teachings are believed to refer to the Qur'an and Hadith.